Readiness for advance care planning and its relationship to coping style in patients with chronic diseases in communities: A cross‐sectional study - Xinru Wang; Yu Sheng (Wiley, 2022)
Abstract Aim This study aimed to assess advance care planning readiness among patients with chronic diseases and identify its relationship to patients' coping styles. Design A cross‐sectional study. Methods Patients with chronic diseases (N = 168) were recruited from community health service centres. We used a self‐designed and validated "advance care planning readiness questionnaire" to measure the patients' advance care planning readiness and a "simplified coping style questionnaire" to measure the patients' coping styles. Results Multiple linear regression analyses observed a positive relationship between "active coping style" (p = .002, 95%CI: 1.788, 7.599) with ACP readiness and a negative relationship between "passive coping style" (p < .001, 95%CI: −10.526, −4.274) with ACP readiness. Our study showed that there was a clear relationship between coping styles and ACP readiness. We suggest encouraging patients to choose more active coping strategies and to explore suitable conversation strategies for different coping styles when facilitating ACP discussion.